1999
DOI: 10.1016/s0014-5793(99)01201-6
|View full text |Cite
|
Sign up to set email alerts
|

Specific loss of chondromodulin‐I gene expression in chondrosarcoma and the suppression of tumor angiogenesis and growth by its recombinant protein in vivo

Abstract: Chondromodulin-I (ChM-I) was previously identified as an angiogenesis inhibitor in cartilage. Here, we demonstrated that the level of ChM-I transcripts was substantially reduced to 100 or even less in the lower-grade chondrosarcomas, in articular cartilage or other benign cartilage tumors. We implanted human chondrosarcoma OUMS-27 cells into nude mice that reproducibly produced tumors with cartilaginous matrix. Tumorinduced angiogenesis was evident when the tumors were excised 30 days after implantation. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 18 publications
2
45
0
2
Order By: Relevance
“…Local administration of recombinant human chondromodulin-I almost completely blocks vascular invasion and tumor growth in vivo. Furthermore, it inhibits the growth of colon adenocarcinoma in vivo, implying therapeutic potential for other solid tumors (123).…”
Section: Non-matrix-derived Inhibitors Of Angiogenesismentioning
confidence: 99%
“…Local administration of recombinant human chondromodulin-I almost completely blocks vascular invasion and tumor growth in vivo. Furthermore, it inhibits the growth of colon adenocarcinoma in vivo, implying therapeutic potential for other solid tumors (123).…”
Section: Non-matrix-derived Inhibitors Of Angiogenesismentioning
confidence: 99%
“…Tumor size was measured with a caliper and tumor volume (TV) was calculated by using a standard formula, TV ϭ width 2 ϫ length ϫ 0.52. 17 After ϳ3 weeks, animals were randomized, into groups each of 3 mice, with comparable tumor size within and among the groups (the TV ranged from 210ϳ260 mm 3 ). The animals were killed at various time points (3, 6 and 16 weeks after inoculation).…”
Section: In Vivo Tumor Modelsmentioning
confidence: 99%
“…16 Chondrosarcomas are usually derived from cartilage, however, they induce tumor angiogenesis in many cases. Hayami et al 17 reported that human chondrosarcoma cell line OUMS-27 18 shows a marked reduction in chondromodulin-I expression, which may explain the lack of the anti-angiogenic property of OUMS-27 cells. Takigawa et al 19 cloned from another human chondrosarcoma cell line HCS-2/8 cells that produced not only anti-angiogenic factors such as chondrocyte-derived inhibitor of angiogenesis and metalloproteinase activity 10 but also an angiogenic factor, connective tissue growth factor.…”
mentioning
confidence: 99%
“…All of the RT reactions were performed using 1 g of total RNA with the SuperScript first strand synthesis system for the RT-PCR kit (Invitrogen). PCR was performed in duplicate for each sample using primers specific for ChM-I (sense, 5Ј-CATCGGGGCCTTCTACTTCT-3Ј; antisense, 5Ј-GGCATGATCTTGCCTTCCAG-3Ј, length 312 bp) (12), Sp1 (sense, 5Ј-CTACCCCTACCTCAAAGGAAC-3Ј; antisense, 5Ј-CTCTCCTTCTTTT-TGCTGGCCT-3Ј, length 821 bp) (13), and Sp3 genes (sense, 5Ј-TTCAGGGAGTTGCAATTGGTG-3Ј; antisense, 5Ј-TTCTGTGCCTG-TGTCTCTTCA-3Ј, length 448 bp) (13). The PCR products were loaded on 1.5% agarose gel and visualized by ethidium bromide staining.…”
Section: Methodsmentioning
confidence: 99%